Proses Penyelesaian Sengketa Delimitasi Maritim di Laut Barents Antara Rusia dan Norwegia - Wismiati, Fiesta Ayu; Kumala Dewi, Putu Ratih; Widya Nugraha, A.A Bagus Surya (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2019)
ABSTRACT The writing of this thesis aims to describe the problem between two countries namely Norway and Russia regarding maritime delimitation conflicts that occur in the Barents sea. The background of this essay writing arises because of the potential contained in the Barents sea, which triggers the existence of different struggles and claims for the region. In addition, the natural wealth contained in the Barents sea is one of the most important places in the world. Natural resources in the region create profits to improve the economy for Russia and Norway, of course. With the conflict between Russia and Norway hampering economic activities to be carried out in the region. The two countries adhere to different principles to the delineation of maritime boundaries which make the journey to resolve this conflict last long. However, the conflict that lasted for 40 years was finally resolved by the two countries through the negotiation process. The following negotiation process will be explained in this paper. Keyword :UNCLOS, Bilateral Agreement Process, Negotiation as a Peaceful Settlement Disputes